2012
DOI: 10.3928/01477447-20120327-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Media in Health Care and Orthopedic Surgery

Abstract: With the growth of social media platforms, their potential to affect health care, and orthopedics specifically, continues to expand. We reviewed the literature to obtain all pertinent information on social media in health care and examined its strengths and weaknesses from patient and physician perspectives. Health care professionals have slowly begun to use social media to stay connected with patients. The recent use of networking sites aims to improve education, provide a forum to discuss relevant medical to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 14 publications
4
50
0
3
Order By: Relevance
“…Third, we have seen an empowerment of patients and an improvement of the health care with more continuous contact (e.g., regarding post-surgery issues) and the use of social media to provide richer communication -such as streaming of instruction videos, etc. These two findings are in line with previous studies on social media and health information retrieval (AlGhamdi & Moussa, 2012), patient empowerment (Lober & Flowers, 2011), and patient education (Saleh et al, 2012). Future research could investigate further the various dimensions of the trends of patient empowerment and health care service improvement observed.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Third, we have seen an empowerment of patients and an improvement of the health care with more continuous contact (e.g., regarding post-surgery issues) and the use of social media to provide richer communication -such as streaming of instruction videos, etc. These two findings are in line with previous studies on social media and health information retrieval (AlGhamdi & Moussa, 2012), patient empowerment (Lober & Flowers, 2011), and patient education (Saleh et al, 2012). Future research could investigate further the various dimensions of the trends of patient empowerment and health care service improvement observed.…”
Section: Resultssupporting
confidence: 90%
“…In a recent study on orthopedic surgery, Saleh et al (2012) have found that "health care professionals have slowly begun to use social media to stay connected with patients. The recent use of networking sites aims to improve education, provide a forum to discuss relevant medical topics, and allow for improved patient care."…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of discussion boards may facilitate patient-doctor or patient-nurse communication [16], may strengthen patients' feelings of control, or - by support of other online members - may encourage lifestyle and health behavior changes. Several forms of online social support targeted at patients undergoing orthopedic surgery or caring for adults with intellectual disabilities have been proposed [16,17]. …”
Section: Potential Of Social Media Use In Clinical Practicementioning
confidence: 99%
“…There has been a commensurate rise in the use of online social networking, social media websites, and online applications: 65 % of American adults (76 % of Internet users) used at least one social networking web site in 2015, compared to only 7 % in 2005 [3]. The average person now engages in social media use for more than 6 hours per week [4]. Approximately 15 % of these users obtain health information through social networking sites [2], with up to 34 % of all adult Internet users having turned to online commentaries, reviews, and blogs to learn about the experience of others with various medical issues or receiving specific treatments [2].…”
Section: Introductionmentioning
confidence: 99%